Access to 6-difluoromethylpyridines by ZnBr2-catalyzed cascade michael addition/ annulation. (22nd January 2021) - Yang, Tianyu; Deng, Zhoubin; Wang, Ke-Hu; Li, Pengfei; Lv, Yuyu; Huang, Danfeng; Shang, Yongwei; Su, Yingpeng; Hu, Yulai
Abstract: A highly efficient ZnBr2 promoted Michael addition/annulation cascade reaction of difluoromethyl- α, β -ynones with β -enamino derivatives has been developed. A series of CHF2 -substituted pyridines has been synthesized by this method from readily accessible raw material in good yields under mild conditions. The 6-difluoromethyl-3-acylpyridines could be further converted into potentially biological active difluoromethylated 4-azafluorenes. Graphical abstract: Image 1 Highlights: Difluoromethyl- α, β -ynones with variously  β -enamino derivatives has been used for the synthesis of 6-difluoromethylpyridines. The 6-difluoromethylpyridines could be further converted into potentially biological difluoromethylated 4-azafluorenes. The protocol has the advantages of readily available starting materials, mild reaction conditions, and high atom economy.